PERLINDUNGAN HUKUM TERHADAP NASABAH PENYIMPAN DANA (DEPOSAN) DALAM BENTUK DEPOSITO DI BANK - Faradila Khairunisa, Jasman Nazar (INTELIGENSIA MEDIA, 2024)
Legal protection for customers who keep funds in the form of deposits in banks aims to protect them from various risks that may occur during deposit transactions. This protection is regulated in the Banking Law and Consumer Protection Law. This research uses a normative method by reviewing and evaluating the applicable laws and regulations. The results show that banks are responsible for compensating customers if their deposit funds are lost. This legal protection is expected to increase customer confidence in banks due to the security of the funds they deposit, thereby reducing the risk of losses and problems in the future.